(untitled) (Journal of the College of Education for Women, 2019)
This paper presents a hybrid software copy protection scheme, the scheme is applied toprevent illegal copying of software by produce a license key which is unique and easy togenerate. This work employs the uniqueness of identification of hard disk in personalcomputer which can get by software to create a license key after treated with SHA-1 one wayhash function. Two mean measures are used to evaluate the proposed method, complexityand processing time, SHA-1 can insure the high complexity to deny the hackers for produceunauthorized copies, many experiments have been executed using different sizes of softwareto calculate the consuming time. The measures show high complexity and short executiontime for proposed combining method.